2019
DOI: 10.1177/2325967119861311
|View full text |Cite
|
Sign up to set email alerts
|

Superior 2-Year Functional Outcomes Among Young Female Athletes After ACL Reconstruction in 10 Return-to-Sport Training Sessions: Comparison of ACL-SPORTS Randomized Controlled Trial With Delaware-Oslo and MOON Cohorts

Abstract: Background: Outcomes after anterior cruciate ligament reconstruction (ACLR) are not uniformly good and are worse among young female athletes. Developing better rehabilitation and return-to-sport training programs and evaluating their outcomes are essential. Purpose: (1) Test the effect of strength, agility, plyometric, and secondary prevention (SAPP) exercises with and without perturbation training (SAPP + PERT) on strength, hops, function, activity levels, and return-to-sport rates in young female athletes 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 54 publications
(112 reference statements)
2
29
2
Order By: Relevance
“…13 Additionally, an investigation by Capin et al concluded that there were no added benefits to including perturbation-based exercises to a post-operative RTS training program that incorporated strengthening, agility and plyometrics among young female athletes after ACL reconstruction. 74 Thus, further investigations of perturbation-based training regimes with various parameters (such as longer duration or increased training intensity) and alternative forms of NM training that combine perturbation training with other exercises that are safe for ACL-injured adolescent females (such as resistance training, cardiovascular conditioning, core strengthening and gait re-education), are still necessary to improve prevention and rehabilitation programs for those at-risk.…”
Section: Resultsmentioning
confidence: 99%
“…13 Additionally, an investigation by Capin et al concluded that there were no added benefits to including perturbation-based exercises to a post-operative RTS training program that incorporated strengthening, agility and plyometrics among young female athletes after ACL reconstruction. 74 Thus, further investigations of perturbation-based training regimes with various parameters (such as longer duration or increased training intensity) and alternative forms of NM training that combine perturbation training with other exercises that are safe for ACL-injured adolescent females (such as resistance training, cardiovascular conditioning, core strengthening and gait re-education), are still necessary to improve prevention and rehabilitation programs for those at-risk.…”
Section: Resultsmentioning
confidence: 99%
“…Our cohort received evidence-based postoperative rehabilitation and the addition of return-to-sport training, which improved all functional outcome measures, including self-reported function, hop testing, and quadriceps strength. 4,5,9,13 Despite these improvements, aberrant gait biomechanics persisted. Our results suggest that current rehabilitation after ACLR may not be adequately targeting gait.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients reached these return-to-sport milestones and subsequently were cleared to begin a return-to-sport progression (pending clearance from the surgeon); all returned to sport within 2 years, most to the same sport level. 9,10…”
Section: Methodsmentioning
confidence: 99%
“…The presence of cross‐cultural DIF is of course most important if data from different countries or cultures are pooled into one dataset. This is typically done in international databases or when national clinical databases are pooled, but also randomized multicentre studies and studies including cohorts in different countries can be affected by cross‐cultural DIF, like the Delaware‐Oslo cohort of ACL patients 6,7 …”
Section: Introductionmentioning
confidence: 99%